Durability of fibre-reinforced cementitious composites (FRCC) including recycled synthetic fibres and rubber aggregates - Cesare Signorini; Andrea Nobili (Applications in Engineering Science, 2022)
We discuss mechanical performance of fibre-reinforced cementitious composites under exposure to four aggressive environments, namely alkaline, saline, sulphuric acid and distilled water immersion. A standard commercial Portland cement based matrix is considered alongside its lightweight modification wherein quarzitic sand is partially replaced by recycled rubber crumbs. Also, virgin polypropylene fibres are contrasted to PP+PET blended fibres where the PET fraction is obtained from recycling food packaging waste. Performance is assessed in bending as well as in compression. We find that recycled based specimens perform surprisingly well and that exposure to the aggressive environments mainly affects the matrix and it is not necessarily more detrimental to the lightweight partially recycled phase. A one-way analysis of variance (ANOVA) confirms the statistical significance of the results, which fully support the idea that the adoption of a substantial recycled fraction in construction materials still allows for high performance and durability standards.